The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ana.23860
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal demyelination and memory dysfunction are associated with increased levels of the neuronal microRNA miR‐124 and reduced AMPA receptors

Abstract: Background Hippocampal demyelination, a common feature of postmortem multiple sclerosis (MS) brains, reduces neuronal gene expression and is a likely contributor to the memory impairment that is found in greater than 40% of individuals with (MS). How demyelination alters neuronal gene expression is unknown. Methods To explore if loss of hippocampal myelin alters expression of neuronal microRNAs (miRNA), we compared miRNA profiles from myelinated and demyelinated hippocampi from postmortem MS brains and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 33 publications
7
143
0
1
Order By: Relevance
“…Second, myelination occurs once axonal synapses are functioning and glutamate and ATP are released for complete myelination of the axons (Nave and Trapp 2008;Nave 2010). This rationale is supported by the decreased levels of miR-124, resulting in increased levels of glutamate receptors during remyelination (Dutta et al 2013). Finally, it is worth mentioning that in some embryos, oligodendrocyte cells were present and expressed mbp as detected by in situ hybridization.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Second, myelination occurs once axonal synapses are functioning and glutamate and ATP are released for complete myelination of the axons (Nave and Trapp 2008;Nave 2010). This rationale is supported by the decreased levels of miR-124, resulting in increased levels of glutamate receptors during remyelination (Dutta et al 2013). Finally, it is worth mentioning that in some embryos, oligodendrocyte cells were present and expressed mbp as detected by in situ hybridization.…”
Section: Discussionmentioning
confidence: 97%
“…Increased levels of miR-124 were detected following demyelination of hippocampal and cortical neurons in MS brains as well as in rodent model of demyelination (Dutta et al 2013), implicating myelin-mediated alteration of neuronal miRNA expression. Conversely, levels of miR-124 were downregulated during remyelination in rodent hippocampus (Dutta et al 2013).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cognitive impairment and memory dysfunction affect more than 60% of MS patients (156). It has been reported that cognitive dysfunction is correlated with hippocampal demyelination (157).…”
Section: Sgz Of the Hippocampusmentioning
confidence: 99%
“…L'utilisation de ces biopuces appliquée à différents tissus provenant de patients atteints de SEP a ainsi mis en évidence une altération de l'expression de nombreux miARN au cours de la maladie. La détection des miARN a été réalisée à partir de tissus (sang total [13,14], tissu nerveux [15,16], hippocampe [17]), de cellules (cellules mononucléées du sang [18][19][20], lymphocytes B [21][22][23] et T [11,20,[23][24][25][26], monocytes [27], microglie [27], cellules endothéliales [28,29]) ou de fluides extracellulaires (sérum/plasma [12,18,[30][31][32][33], LCR [34]). Nous répertorions de manière systématique dans cette revue, l'ensemble des données issues de la littérature concernant les miARN SYNTHÈSE REVUES miR-155 -/- [37]) sont résistantes à l'induction d'une EAE.…”
Section: Dérégulation Des Miarn Chez Les Patients Atteints De Sepunclassified